Fenomena Pemberian Makanan Gratis di Masjid Al-Athas Rendeng Kudus pada Hari Jum’at dan Korelasinya dengan Q.S Al-Baqarah Ayat 274 - Arlana, Alvian Yul; Saerozi, Ahmad (Lembaga Penelitian dan Pengabdian kepada Masyarakat (Center for Research and Community Services), Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2025)
This article aims to reveal one of the phenomena that occurred at the Al-Athas Rendeng Mosque, Kudus, namely food intended for Friday prayer congregations. This study attempts to reveal the history of the provision of free food at the mosque, from whom the free food was placed in the mosque and their motivations, and what impacts resulted from the phenomenon of the emergence of free food that is happening now. The research used was qualitative research with the type of field research and the theory used was symbolic interactionism. The results of the study concluded that; The Al-Athas Rendeng Kudus Mosque functions as a center for distributing free food after Friday prayers, an initiative of sugar factory employees, which aims to strengthen solidarity and the values of the Qur'an. The donors consist of regular donors and volunteers, who donate as a form of prayer and follow the teachings to give alms. This program is very helpful for the congregation, especially those who come from far away, and creates an atmosphere of togetherness. Free food not only meets physical needs, but also strengthens social relationships among the congregation. Overall, this initiative shows the importance of concern and support among Muslims, improving community welfare.